Simulasi pengaruh bentuk piston bowl dan dome terhadap perubahan sifat mekanik menggunakan software Ansys dengan metode finite element analysis - Zukfikar, M.P.; Setyawan, P.D; Rachmanto, T. (Universitas Mataram, 2024)
A piston is a component of an internal combustion engine. This study numerically investigated variations in the shape of the piston head to determine mechanical changes affected by static surface pressure and temperature. The method used is FEA (Finite Element Analysis) with steady-state thermal and static structural simulations. This study aims to determine the effect of changes in the shape of the Piston Head Bowl and Piston Head Dome on the value of Von Mises stress, strain, deformation, and safety factors using Ansys software. This research was conducted numerically with a variety of concave piston heads (bowl) with surface lengths of 3 mm, 5 mm, 7 mm, 9 mm, and 12 mm with a depth of 1.2 mm and convex piston heads (dome) with surface lengths of 3 mm, 5 mm, 7 mm, 9 mm, and 12 mm with a slope of 182⁰. The results showed that the variation of piston head shape affects the value of von Mises stress, strain, deformation, and safety factor. where the convex piston head (dome) has a lower von Mises stress value and maximum strain than the concave piston head (bowl), the deformation value of the dome piston head is higher, and the minimum safety factor value of the dome piston is higher. The lowest Von Mises stress value is 611.42 MPa on the piston head dome, the maximum strain value is 0.007741, the highest maximum deformation value is 0.055 mm on the piston head dome with a surface length of 12 mm, and the best minimum safety factor value is 0.515 on the piston head dome.